32.2: Invited Paper: Fast Switching Blue Phase Liquid Crystals. (4th October 2019) - Feng, Yifan; Cha, Shenghao; Sun, Changli; Lu, Jiangang
Abstract : Several recent advances to improve the optical‐electrical properties of blue phase liquid crystals (BPLCs) were proposed. A critical temperature is demonstrated in the phase transition of BPLC, which affects the lattice formation process. Polymer materials with the reactive diluent was investigated which may increase the Kerr constant and decrease the response time. And a conductive polymer dopant was introduced into PS‐BPLCs which may much improved driving capacity without degradation response time, hysteresis and residual birefringence.